Abelhas e suas relações ecológicas como temas geradores no ensino de Ciências em uma escola rural de Campo Grande/MS - Costa, Lauriane Magalhães da (2021)
The research has as one of its objectives to provide students with information that expands their knowledge about insects and the Cerrado Biome so that they can form critical thinking about the importance of associating bees and other living beings necessary for the balance of ecosystems. Participants in this research were students from sixth to eighth grade, elementary school classes from the Darthesy Novaes Caminha Municipal School, located in the rural area of Campo Grande/MS. Due to the pandemic of the new coronavirus - SARS-CoV-2 and the need for remote classes, the methodology had to be changed and adaptations emerged to meet this new reality. We opted for the use of an instant messaging application, WhatsApp, an informal language widely used by people of different age groups, and the online platform Google Classroom for the online classes. The sequence of classes consisted of activities focused on the science content that deals with insects, including their ecological importance, morphology, and classification. This theme was also used in the production of the BeeApp educational application for cell phones and computers,an application specially developed for the research. In the present project, the research was carried out based on generating themes, in the Freirian educational conception. The methodological process used corresponded to the qualitative approach, where the activities developed were remote practical and theoretical classes about insects found in the Cerrado and their ecological importance for the environment. In addition to the application of questionnaires, collection, classification of insects, and construction of an entomological box. Through the investigative process, it was found that during the development of the activities a relationship of appreciation and trust was built, establishing a significant link in the process of building knowledge among the participants. Thus, it was noticed that the construction of scientific knowledge in the area of Environmental Education can occur in a more interesting and significant way inside or outside the classroom, in urban or rural environments by means of didactic-pedagogical elements such as videos, audios, text messages, images, and educational applications. It is also concluded that more studies are needed on the use of innovative methodologies in public schools, as well as on the training of education professionals in the technological area and investments by the government in didactic resources based on technology.